Utilization of Big Data In E-Commerce Business - Nico Fernando; Mery Mery; Jessica Jessica; Johanes Fernandes Andry (IAIC Publishing, 2020)
In this day and age with the internet brings revolution to the way all fields work, especially in the field of business. With the internet technology data became big and known as